Metaphors, Visual Blends and the Ideology of Information Technology - Rohrer, Tim (HERMES - Journal of Language and Communication in Business, 2000)
In this article I argue from linguistic and visual evidence that the information highway metaphor is having tremendous ideological effects in shaping U.S. politics over technology. I apply Lakoff and Johnson’s theory of conceptual metaphor to the linguistic and visual evidence, but then argue that Fauconnier and Turner’s theory of conceptual blending is useful to explain the visual and linguistic evidence in its full complexity. I conclude by summarizing the ways in which current ideological uses of conceptual metaphors and conceptual blends are assimilating the older innovative software design metaphors for operating systems.